SME financing in Iceland: an empirical study of capital structure and the financing environment of SME's in Iceland - Vala Hrönn Guðmundsdóttir 1989- (2015)
The thesis analyses the capital structure decisions of Icelandic SME‘s and how market participants perceive the Icelandic finaning environment by surveying CEO‘s and interviewing market participants. The research finds that capital structure decisions conform most to the financial growth cycle and pecking order theories. Firms prefer internal financing,then debt and finally equity. It is difficult to determine whether they make these choices out of preference and assymetric information(POT) or because they have limited access to other options(FGC). There are two active securities markets in Iceland, Nasdaq‘s main market and First North. Although many neighbouring countries have thriving markets such as First North where SME‘s are traded, only three firms are registered on Iceland‘s First North. Many believe that this is a result of the financial collapse of 2008 and that the markets still have a long way to go to recover their trust and reputation in the eyes of public investors. Interviews reveal that respondents feel that access to financing is limited. Bank debt is not available without solid collateral or cash flows, and few active venture capital funds or private investors exist. More options as well as suppliers of financing are needed to enhance the SME sector, something very important for future economic growth in Iceland. Access to financing highly restricts Icelandic SME‘s and their abilities to make sophisticated financing choices and to conduct strategic financial management. The research finds that Iceland has a very strong base environment for founding companies, but does not follow through in later stages and that firms, especially high-growth ones, have problems funding growth. Capital controls deter foreign investment and the financing environment is still very damaged from a financial collapse in 2008. Most institutions and regulatory parties are crippled by strict supervision, limiting their abilities to rebuild their processes and protocols. Trust and reputation must be rebuilt in order to ...